2013
DOI: 10.18052/www.scipress.com/ilshs.6.24
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Housing in Rural Villages: The Case Northeastern Montenegro

Abstract: The paper analyzes the basic characteristics of housing in rural areas of northeastern Montenegro, based on examples from Berane, Andrejevica and Plav. People in rural areas northeastern of Montenegro are in accordance with their modest lifestyle, built by the simple but functional living quarters. The chronology of the type of housing facilities is differentiated into morphological types of permanent residence: primitive forms of human habitats (dugouts -cave dwellings, semi dugouts); a more perfect forms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Due to the lack of data for the production of meat in Montenegro in 2010, we used the data of the Statistical Office of Montenegro [22] in 2001/02. Before than we approach view the current state of animal husbandry in Montenegro, it is important to stress that livestock farming is a significant potential for agricultural development, but is underdeveloped in relation to natural resources and the demands of intensive agricultural production [23][24][25] .…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of data for the production of meat in Montenegro in 2010, we used the data of the Statistical Office of Montenegro [22] in 2001/02. Before than we approach view the current state of animal husbandry in Montenegro, it is important to stress that livestock farming is a significant potential for agricultural development, but is underdeveloped in relation to natural resources and the demands of intensive agricultural production [23][24][25] .…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Responsible role in formulating rural development in Montenegro, which will be based on the natural and socioeconomic potential of rural areas, should certainly have and geographical Sciences, who their access should to consolidate research efforts and the results of other scientific disciplines [47][48][49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Classification method enabled us to systematic and complete separation of the general terms on the special, which includes the concept. The method of systematization and generalization implied is cognitive processes of abstraction [20][21][22]. The method of analysis was related to study and explanation of reality partition of complex thought creation on their simple components.…”
Section: Methodsmentioning
confidence: 99%
“…Above mentioned books are gives historical -sociological view Gnjili Potok and constitute a modest contribution to the understanding of these issues, so we as such during our research we used. Further, studies of rural villages Gnjili Potok, continue the authors of this text, both at the level of the village and at the level of the local community of the Kralje and as a result of the resulting texts: "Rural village Gnjili Potok as a reflection of the socio-economic conditions" [4], "Destinations freshwater fishing, Rajova River harsh and beautiful" [5], "Tourist Potential on Example of Rural Settlement Gnjili Potok (Montenegro)" [6]," Geographical starting points the analysis of current rural problems in Montenegro: A case study of the rural settlement of Gnjili Potok" [7], "Rural village Gnjili Potok -road sign towards happiness and freedom (Some geographical aspects of sustainable development)" [8], "Some Economic -Geographical Factors Development: The Case of Local Communities Kralje" [9], "Geographic Favor of Analyzing Rural Space: The Case Rural Local Communities Kralje" [10], Geographical Starting Points The Analysis Of Current Rural Problems In Montenegro: Case Study Of Rural Local Community Kralje" [11], monograph "Natural and socio economic characteristics of rural villages Gnjili Potok" [12].…”
Section: Introductionmentioning
confidence: 99%
“…The core methodological procedure used in this study is the geographic (spatial) method, whose scope of research has related to the municipality Berane, Andrijevica and Plav. It is in fact geographical unit which comprises 10,8 % of the total area of Montenegro (13.812 km²), that is, living in the territory, 8,12% (54.658 population) of the population compared to the total population of Montenegro in 2003 (673.094) [11][12]. Place in the research I have found their following methods: descriptive, a causal, comparative method and theoretical analysis.…”
Section: Methodsmentioning
confidence: 99%